Authoritarian Institutions and Democratic Lessons. (June 2023) - Yadav, Vineeta
Does the experiential legacy of participating in autocratic legislatures influence how autocratic-era opposition parties and politicians want to use legislatures in a subsequent democracy? Do they learn to use legislatures to strengthen or undermine democracy? Given the frequency of institutionalized autocracies, of opposition party led post-transition governments, and importance of legislatures in democracies these are important questions. This paper addresses them by first drawing on research on authoritarian legacies, and on organizational and individual learning to identify three potential institutional lessons opposition parties and politicians could learn from their autocratic legislative experience about how to use legislatures in a subsequent democracy. It then uses data from a survey of almost 200 Egyptian politicians conducted during the 2011 elections to test which lessons parties and politicians learned by focusing on their support for protecting judicial independence from legislative interference in the future democratic regime. We find that (i) experienced opposition parties learn a democracy-strengthening institutional lesson, (ii) experienced opposition politicians learn a democracy-weakening institutional lesson, and (iii) membership in an experienced opposition party curbed the undemocratic institutional preferences of experienced politicians. Thus, authoritarian institutions leave diverse legacies among ruling and opposition parties and politicians with very different consequences for subsequent democracy.